Teaching Transnational Buddhist Meditation with Vipassanā (Neiguan 內觀) and Mindfulness (Zhengnian 正念) for Healing Depression in Contemporary China - Ngar-sze Lau (Religions, 2021)
This paper examines how the teaching of embodied practices of transnational Buddhist meditation has been designated for healing depression explicitly in contemporary Chinese Buddhist communities with the influences of Buddhist modernism in Southeast Asia and globalization. Despite the revival of traditional Chan school meditation practices since the Open Policy, various transnational lay meditation practices, such as vipassanā and mindfulness, have been popularized in monastic and lay communities as a trendy way to heal physical and mental suffering in mainland China. Drawing from a recent ethnographic study of a meditation retreat held at a Chinese Buddhist monastery in South China, this paper examines how Buddhist monastics have promoted a hybrid mode of embodied Buddhist meditation practices, mindfulness and psychoanalytic exercises for healing depression in lay people. With analysis of the teaching and approach of the retreat guided by well-educated Chinese meditation monastics, I argue that some young generation Buddhist communities have contributed to giving active responses towards the recent yearning for individualized bodily practices and the social trend of the “subjective turn” and self-reflexivity in contemporary Chinese society. The hybrid inclusion of mindfulness exercises from secular programs and psychoanalytic exercises into a vipassanā meditation retreat may reflect an attempt to re-contextualize meditation in Chinese Buddhism.